EFFECT OF VARIATIONS OF NaCl QUENCHING MEDIA ON LOW AISI 1020 CARBON STEEL WITH CARBURIZING PROCESS - Firdaus MS; Wahyu Wiranata; Sugeng Prasetyo (Jurnal Teknik Mesin dan Mekatronika (Journal of Mechanical Engineering and Mechatronics), 2022)
This study aims to determine the effect of variations in quenching media with NaCl on the value of hardness, energy value of the impact and the microstructure phase formed from the carburizing pack. The results showed that the highest hardness value was obtained by quenching 25% NaCl with a value of 136.76 N/mm2 and the lowest value was obtained in specimens without raw material treatment with a value of 119.63 N/mm2, it can be concluded that the higher the concentration of salt, the higher the hardness value. The results of the impack test showed the highest value in the Raw Material specimen with a value of 14,234 Joules and the lowest value on the specimen with 25% NaCl quenching with a value of 5,694 Joules, it can be concluded that the untreated specimen has a good ductility value, while for the specimens undergoing the quenching process, experience agitation. Metallographic test results show the phase of martensive formation in the quenching process and ferlite in Raw Material